Definition of formulation design space, in vitro bioactivity and in vivo biodistribution for hydrophilic drug loaded PLGA/PEO-PPO-PEO nanoparticles using OFAT experiments - Simonoska Crcarevska, M; Geskovski, N; Calis, S; Dimchevska, S; Kuzmanovska, S; Petruševski, G; Kajdžanoska, M; Ugarkovic, S; Goracinova, K (Elsevier BV, 2013)
Modified nanoprecipitation method was used for improved incorporation of hydrophilic drug (irinotecan hydrochloride) into the PLGA/PEO-PPO-PEO blended and blended/adsorbed nanoparticles. One factor at a time (OFAT) variation experiments were conducted in order to determine key formulation factors (concentration and volume of drug solution, evaporation rate and PLGA/PEO-PPO-PEO ratio) influencing nanoparticle properties (particle size and size distribution, encapsulation efficiency, drug content, zeta potential, drug dissolution rate, as well as protein binding capacity). The insight into in vivo behavior of prepared nanoparticles and their potential for effective anticancer treatment was gained by performing biodistribution and cell culture studies as part of OFAT experiments. The mean particle size, mainly dependent upon PLGA/PEO-PPO-PEO ratio, was in the range of 112-125 nm, with narrow unimodal distribution (PDI∼0.1). Encapsulation efficiency (32-63%) was impacted by evaporation rate and PLGA/PEO-PPO-PEO ratio. Drug content (0.2-1.51%) and controlled release properties were related to the influence of all tested formulation factors. Structural information for the studied nanoparticles was obtained using DSC and FT-IR spectroscopy. Zeta potential values indicated that presence of PEO-PPO-PEO in the formulations shielded the high surface negative charge of PLGA. PEO-PPO-PEO surface coverage of PLGA/PEO-PPO-PEO blended as well as blended/adsorbed nanoparticles depended upon amount of used PEO-PPO-PEO during preparation procedure and was related to the protein resistant characteristics of nanoparticles. Results from in vivo studies evidenced prolonged blood circulation time of the prepared nanoparticles, while cell culture studies indicated higher in vitro bioefficacy compared to free drug. Performed experiments defined possible design space and justified further optimization of formulation using experimental design studies.